2014
DOI: 10.1007/s40521-014-0022-0
|View full text |Cite
|
Sign up to set email alerts
|

Galactose-Alpha-1,3-Galactose, Mammalian Meat and Anaphylaxis: A World-Wide Phenomenon?

Abstract: Opinion StatementMammalian meat allergy following tick bites is known to occur in Australia, North America, Europe, Asia, Africa and Central America. Over the last decade, the condition has become increasingly prevalent in tick-endemic areas of Australia and the USA. In mammalian meat-allergic individuals, gelatine allergy and/or cow's milk allergy may co-exist. Awareness of tick-induced allergies in health professionals and the general community is key to both a timely diagnosis and the prevention of mammalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Tick‐induced allergies comprise large local reactions to tick bites, mammalian meat allergy after tick bites, and tick anaphylaxis 1 , 2 . Ixodes holocyclus (the Australian paralysis tick) (Box 1) is responsible for the majority of bites in humans in Australia and is therefore the tick that causes most tick‐induced allergies 3 .…”
Section: Spectrum Of Tick‐induced Allergiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tick‐induced allergies comprise large local reactions to tick bites, mammalian meat allergy after tick bites, and tick anaphylaxis 1 , 2 . Ixodes holocyclus (the Australian paralysis tick) (Box 1) is responsible for the majority of bites in humans in Australia and is therefore the tick that causes most tick‐induced allergies 3 .…”
Section: Spectrum Of Tick‐induced Allergiesmentioning
confidence: 99%
“…Large local allergic reactions to tick bites, while incapacitating at the time, are the least severe form of tick‐induced allergies. The commonest presentation of a serious tick‐induced allergy is mammalian meat allergy after a tick bite, which may manifest as anaphylaxis, recurrent angioedema or gut symptoms after ingestion of mammalian meat — all typically delayed by 3–6 hours 1 , 2 , 4 . ‐ 6 Mammalian meat allergy is an emergent allergy that has become increasingly prevalent in tick‐endemic areas of Australia and the United States, and has been reported worldwide where Ixodes spp, Amblyomma spp and Haemaphysalis longicornis are endemic and known to bite humans (Box 2).…”
Section: Spectrum Of Tick‐induced Allergiesmentioning
confidence: 99%
“…A recent Australian study demonstrated confirmed FA incidence at age 12 months to be 10% with lower estimates for older children of 3–5% and 1–3% in adults in other studies . Anaphylaxis to stinging insects may occur (bees, wasps, Jack Jumper ants) and in some regions, from tick bites as well . Allergy to medications or latex are less common in childhood.…”
Section: Reducing the Risk Of Anaphylaxis: Key Principlesmentioning
confidence: 99%
“…4 Anaphylaxis to stinging insects may occur (bees, wasps, Jack Jumper ants) and in some regions, from tick bites as well. 5 Allergy to medications or latex are less common in childhood.…”
mentioning
confidence: 99%
“…16,17 AGS is characterized by delayed anaphylaxis to red meat consumption and certain drugs, such as cetuximab, and immediate anaphylaxis to tick bites, and is becoming a global problem with increasing prevalence in all continents and with the involvement of several tick species. [16][17][18][19][20] Humans do not produce the carbohydrate α-Gal (Gal α 1-3Gal β 1-(3)4GlcNAc-R), 21 and the not yet fully understood immune response induced by tick bites that includes anti-α-Gal IgE antibodies break the oral tolerance to food allergens, resulting in a gut-related but not lung-related allergy. 16,20 The GGTA1 gene encoding for the α1,3-galactosyltransferase enzyme that synthetizes α-Gal in mammals was inactivated in humans, apes and Old World monkeys approximately 28 million years ago.…”
mentioning
confidence: 99%